Development of chromatographic methods through the lens of green chemistry - Natalija Nakov, Jelena Acevska, Katerina Brezovska, Jasmina Tonikj-Ribarska (Faculty of Technology and Metallurgy, University Ss. Cyril and Methodius in Skopje, 2024)
Reverse-phase high-performance liquid chromatography (RP-HPLC) is one of the most commonly used techniques in pharmaceutical analysis, playing a fundamental role in the pharmaceutical industry. The conventional LC methods often use large quantities of toxic organic solvents for sample preparation and as part of the LC mobile phase. The increasing awareness, but also the concern about the negative effects of chemicals and chemical waste generated from the conventional chromatographic methods have led to the adoption of green analytical chemistry (GAC) principles in pharmaceutical analysis. Green LC, a part of GAC, is aimed at finding new eco-friendly organic solvents to replace harmful ones, with the goal of creating sustainable chromatographic methods. In this research, several sustainable RP-HPLC methods for quality control of medicinal products were developed. Greening of the LC methods was achieved by replacing toxic solvents (acetonitrile and methanol) with ethanol, as the most preferred green solvent. In addition, the reduction of the solvent consumption was introduced with the use of smaller solvent quantities for the sample preparation process. The methods were validated according to the ICH guideline and applied for quality control of the medicinal products. The evaluation of the methods’ greenness features was performed using the Eco-scale index, the AMGC calculator and the Analytical GREEnness metric. The sustainability (“whiteness”) of the proposed RP-HPLC methods was confirmed using the RBG 12 algorithm. The findings confirmed that the ecological aspects of the chromatographic method can be improved, while preserving/improving the required analytical and economical attributes of the method.
Keywords: green analytical chemistry, eco-friendly chromatographic methods, pharmaceutical analysis, greenness assessment